CALQUE-FREE LECTURES? SPANISH CROSS-LINGUISTIC INFLUENCE IN CONTENT TEACHING THROUGH ENGLISH - Braga Riera, Jorge; Domínguez Romero, Elena (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In the last ten years, Spanish universities have gradually started to incorporate English as a means of instruction. As a result, many lecturers — who regularly use their mother tongue for their teaching activity— have been compelled to adapt their syllabus contents into English, resulting in lectures that show vidence of cross-linguistic influence (Odlin, 1989). This is especially noticeable in the recurrent presence of calques, which emerge as a consequence of both the teachers’ insufficient proficiency in the foreign language and a lack of expertise in lecturing through a non-native medium of spoken communication. The goal of this paper is precisely to evaluate the extent to which this interference is made visible. To this aim, a corpus of three Engineering lectures delivered in English has been used as a means of exemplification, with results that prove the presence of syntactic, lexical and morphological calques in all cases. The ultimate end of this research is not only to raise teachers’ awareness of their own dependency on L1 as their main language resource, but also to eventually provide them with tools and strategies which might enhance their performance, hence improving teacherstudent communication. Resumen En los últimos diez años, las universidades españolas han empezado a incorporar el inglés como lengua para la docencia. Como resultado, muchos profesores —acostumbrados a enseñar en su lengua materna— se han visto obligados a adaptar los contenidos de sus programas al inglés, con la consiguiente influencia cros-lingüística en el desarrollo de su actividad docente (Odlin, 1989). Esto se aprecia especialmente en la presencia recurrente de calcos, consecuencia tanto de la falta de conocimiento lingüístico de los profesores a la hora de transmitir conocimientos en una lengua extranjera como de su escasa experiencia en este sentido. El objetivo de este trabajo es precisamente analizar hasta qué punto esta interferencia se hace realmente patente en el aula. Con esta intención, y a modo de ejemplo, se ha utilizado un corpus formado por tres clases de Ingeniería impartidas en inglés. Los resultados del análisis revelan que todas ellas presentan calcos sintácticos, léxicos y morfológicos. El objetivo último de este trabajo no es sólo concienciar a los profesores de su dependencia de la lengua materna como primer recurso lingüístico, sino también dotarlos con herramientas y estrategias que les permitan mejorar su actividad, lo que sin duda repercutirá en una comunicación profesor-estudiante más óptima.